Feline coronavirus influences the biogenesis and composition of extracellular vesicles derived from CRFK cells - Wijerathne, Sandani V. T.; Pandit, Rachana; Ipinmoroti, Ayodeji O.; Crenshaw, Brennetta J.; Matthews, Qiana L. (Frontiers in Veterinary Science, 2024)
Introduction: Coronavirus (CoV) has become a public health crisis that causes numerous illnesses in humans and certain animals. Studies have identified the small, lipid-bound structures called extracellular vesicles (EVs) as the mechanism through which viruses can enter host cells, spread, and evade the host's immune defenses. EVs are able to package and carry numerous viral compounds, including proteins, genetic substances, lipids, and receptor proteins. We proposed that the coronavirus could alter EV production and content, as well as influence EV biogenesis and composition in host cells.In the current research, Crandell-Rees feline kidney (CRFK) cells were infected with feline coronavirus (FCoV) in an exosome-free media at a multiplicity of infection (MOI) of 2500 infectious units (IFU) at 48h and 72h time points. Cell viability was analyzed and found to be significantly decreased by 9% (48h) and 15% (72h) due to FCoV infection. EVs were isolated by ultracentrifugation, and the surface morphology of isolated EVs was analyzed via Scanning Electron Microscope (SEM).Results: NanoSight particle tracking analysis (NTA) confirmed that the mean particle sizes of control EVs were 131.9 nm and 126.6 nm, while FCoV infected-derived EVs were 143.4 nm and 120.9 nm at 48h and 72h, respectively. Total DNA, RNA, and protein levels were determined in isolated EVs at both incubation time points; however, total protein was significantly increased at 48h. Expression of specific protein markers such as TMPRSS2, ACE2, Alix, TSG101, CDs (29,47,63), TLRs (3,6,7), TNF-α, and others were altered in infection-derived EVs when compared to control-derived EVs after FCoV infection.Discussion: Our findings suggested that FCoV infection could alter the EV production and composition in host cells, which affects the infection progression and disease evolution. One purpose of studying EVs in various animal coronaviruses that are in close contact with humans is to provide significant information about disease development, transmission, and adaptation.Hence, this study suggests that EVs could provide diagnostic and therapeutic applications in 2 animal CoVs, and such understanding could provide information to prevent future coronavirus outbreaks.